Effect of length of stay in intensive care unit on hospital and long-term mortality of critically ill adult patients - Williams, Teresa; Ho, K.; Dobb, G.; Finn, Judith; Knuiman, M.; Webb, S. (Oxford University Press, 2010)
Critical illness leading to prolonged length of stay (LOS) in an intensive care unit (ICU) is associated with significant mortality and resource utilization. This study assessed the independent effect of ICU LOS on in-hospital and long-term mortality after hospital discharge. Most hospital deaths occurred within the first few days of ICU admission. Increasing LOS in ICU was not associated with an increased risk of in-hospital mortality after adjusting for other covariates, but was associated with an increased risk of long-term mortality after hospital discharge. The variability on the long-term mortality effect associated with ICU LOS (2.3%) appeared to reach a plateau after the first 20 days in ICU and was not as important as age (35.8%), co-morbidities (18.6%), diagnosis (10.9%), and APS (3.6%)